THE TRANSFORMATION MODEL OF ISLAMIC BOARDING SCHOOLS IN CURRICULUM DEVELOPMENT SEEN FROM LOCAL RELIGIOSITY TOWARDS GLOBAL IDEALITY AT THE RAUDLOH AL THOHIRIYAH ISLAMIC BOARDING SCHOOL KAJEN PATI - Syafiq, Abdullah; Rahardja, Edy (JURNAL BISNIS STRATEGI, 2023)
The transformation model of pesantren education in curriculum development is seen from local religiosity towards global ideality at the Raudloh Al Thohiriyah Kajen Pati Islamic boarding school. Regarding the transformation of education in curriculum development, based on the description and existing problems, this study has the following objectives: 1). To knoweducational transformation model of the Raudloh Al Thohiriyah Kajen Pati Islamic boarding school, and 2) To find out the implementation in the development of the Raudloh Al Thohiriyah Kajen Pati Islamic boarding school curriculum seen from local religiosity towards global ideals. The data collection method in this thesis in this study will later use a qualitative research methodology with a participatory approach through multilevel stages,then EngineeringAnalysis of this data using analysis (Triangulation) is described. Triangulation analysis is an attempt to synthesize and group data from observations, interviews, and FGDs.in this research is descriptiveanalytical.The results of this study conclude that 1) Transformation of the educational curriculum has a very important role and use, because this curriculum transformation directs all educational activities carried out by an institution. 2) The main factor inhibiting educational transformation is the conservative view. The meaning is that the current situation is the best and does not need to be changed. This view is still held by some Islamic boarding school caretakers, resulting in setbacks. 3) Development of curriculum materials to improve the quality of education at the Raudloh Al Thohiriyah (Al Mardliyah) Islamic Boarding School of Kajen Pati comes from the curriculum components and learning completeness, curriculum content, local content, self-development, life skills education, study load regulation.